Coffee production during the transition period from monoculture to agroforestry systems in near optimal growing conditions, in Yunnan Province - Rigal, C.; Xu, J.; Hu, G.; Qiu, M.; Vaast, Philippe (Elsevier, 2020)
Large-scale conversions from monoculture arabica coffee systems to agroforestry systems started in 2012 in southern Yunnan Province. This study analyses the impact of young shade trees (Cinnamomum camphora, Bishofia javanica and Jacaranda mimosifolia) on microclimate, coffee fruit development cycle, coffee yield, and coffee quality only 4 years after their introduction. The results show that young shade trees reduced diurnal fluctuations in temperatures, buffered high temperatures in the rainy season (−3 to −6 °C), and protected coffee trees from cold temperatures in the dry season (+0.5 to +1 °C). Coffee flower set decreased with shade intensity, as did fruit losses during the bean filling and maturation stages. Consequently, coffee trees under B. javanica and J. mimosifolia, which both provide light shade intensity, produced yields similar to those of coffee trees in open conditions. Only coffee trees under the dense shade of C. camphora had lower yields. Shade trees did not affect the physical and organoleptic attributes of coffee beans. This study hence demonstrates that carefully selected shade trees can rapidly provide positive ecosystem services related to microclimate and coffee physiology, while maintaining a coffee yield and quality similar to those found in monoculture coffee systems. With their diffused shade, B. javanica and J. mimosifolia are suitable options for the agro-ecological intensification of coffee systems, while the use of C. camphora requires active management and pruning practices in order to sustain high coffee yield.